The influence of timing of oocytes retrieval and embryo transfer on the IVF-ET outcomes in patients having bilateral salpingectomy due to bilateral hydrosalpinx - Yilei, He; Shuo, Yang; Caihong, Ma; Yan, Yang; Xueling, Song; Jiajia, Zhang; Ping, Liu; Rong, Li; Jie, Qiao (Frontiers in Surgery, 2023)
Objective To investigate whether the sequence of oocyte retrieval and salpingectomy for hydrosalpinx affects pregnancy outcomes of IVF-ET patients. Study Design There were 1,610 bilateral hydrosalpinx patients who underwent laparoscopy salpingectomy and IVF-ET/ICSI from January 2009 to December 2018. They were divided into two groups: oocyte retrieval first group: 235 accepted oocyte retrieval before salpingectomy; operation first group: 1,375 accepted oocyte retrieval after salpingectomy. The basic information and pregnancy outcomes of the two groups were compared. The pregnancy outcomes and influencing factors were analyzed among patients at different starting times of FET or oocyte retrieval after the salpingectomy. Results Patients in the oocyte retrieval first group had higher levels of basal FSH and lower AMH levels (P<0.05). There were no cases of pelvic infection or oocyte and embryo contamination after oocyte retrieval in the oocyte retrieval first group. In the frozen cycle, the clinical pregnancy and miscarriage rates of the oocyte retrieval first group were lower than those in the operation first group (P<0.05), while the live birth rate was not significantly different (P>0.05). The live birth rates of patients ≥ 35 years old in the operation first group and the oocyte retrieval first group were not significantly different (29.3% vs. 23.3%, P=0.240). After adjusting for age and AFC, oocyte retrieval 4-6 months and 7-12 months after the operation had higher accumulated pregnancy rates (OR 1.439 (1.045-1.982), P=0.026; OR 1.509 (1.055-2.158), P=0.024) and higher accumulated live birth rates (OR 1.419 (1.018-1.977), P=0.039; OR 1.544 (1.068-2.230), P=0.021). No significant difference was observed in the pregnancy outcomes of frozen embryo transfer at different times after salpingectomy (P>0.05). Conclusion No contamination of the embryo or infection was observed in patients who underwent oocyte retrieval before the operation. The interval between the operation and frozen embryo transfer did not affect the pregnancy outcomes. After adjusting for age and AFC, patients who underwent oocyte retrieval 4-6 months and 7-12 months after the operation had higher accumulated pregnancy rates and live birth rates.